Dual-energy CT and coronary imaging - Kay, Fernando Uliana (Cardiovasc Diagn Ther, 2020)
Dual-energy computed tomography has been proposed for enhancing the evaluation of coronary artery disease in many fronts. However, the clinical translation of such applications has followed a slower pace of clinical translation. This paper will review the evidence supporting the use of dual-energy computed tomography in coronary artery disease (CAD) and provide some practical illustrations, while underscoring the challenges and gaps in knowledge that have contributed to this phenomenon.